Електронне портфоліо та його сприяння навчанню студентів - Ситнік, Н. О. (ХНУРЕ, 2023)
This work describes the benefits of e-portfolios in promoting student learning. One can regard an e-portfolio as a type of learning record that provides actual evidence of achievement. Learning records are closely related to the learning plan, an emerging tool which individuals, teams, communities of interest, and organizations use to manage learning. To the extent that a personal learning environment captures and displays a learning record, it may also operate as an electronic portfolio. E-portfolios, like traditional portfolios, can facilitate students' reflection on their own learning, leading to more awareness of learning needs.